DEHUMANIZING CASTE IN PERUMAL MURUGAN'S PYRE - P. Karthikeyan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The topic of the paper is one that is hotly debated in the current context for its kind. Although the novel's female protagonist Saroja's caste was not specifically mentioned by author Perumal Murugan, readers are likely to wonder "which caste does she belong to?" based on firsthand accounts. The goal of the paper is to uncover the shaky perceptions of the lumpen human race that twirls while grasping a string. The helpless characters of Murugan who do not challenge the injustice and callous attitudes of the locals are also criticized in the paper. This essay on Pyre, also known as Pookkuzhi, seeks to contextualize the oppressions and dehumanization of the marginalized human development.